Effect of Magnetically Treated Water on Physiological and Biochemical Blood Parameters of Japanese Quail - Al-Hilali , Ali H. (International Journal of Poultry Science, 2018)
Objective: The present study examined the effect of magnetically treated water (MTW) on the physiology and biochemistry of Japanese quail to increase the production of poultry in Iraq. Materials and Methods: Sixty male Japanese quail were divided into three groups and given tap water treated with a 0 (control), 500 (T1), or 1000 (T2) Gauss magnetic field for 60 days. Changes in the chemical and physical properties of the water were examined with and without magnetization. Biochemical and physiological parameters measured in quail included red and white blood cell counts (RBCs and WBCs, respectively), packed cell volume (PCV), hemoglobin (Hb), cholesterol, lactate dehydrogenase (LDH), very low density lipoprotein (VLDL), low density lipoprotein (LDL), triglycerides, glucose, total protein levels, aspartate transferase, alanine transferase, alkaline phosphatase (AP) activity, aspartate transaminase (AST), alanine aminotransferase (ALT) and the mitotic index. Results: Magnetic treatment of water significantly increased RBCs, WBCs, Hb, PCV%, total protein levels, AP activity and the mitotic index but caused a significant decline in total cholesterol, LDL, VLDL, triglycerides, glutathione (GSH) and glucose levels. There were no significant differences in aspartate or alanine transferase activity between either treatment groups compared to control. Conclusion: The results indicate that MTW improved all biochemical and physiological properties of Japanese quail, which could help to improve poultry productivity.